COMPARISON OF EFFECTIVENESS OF EXERCISE THERAPY VERSUS TRANSCUTANEOUS ELECTRICAL NERVE STIMULATION IN PAIN MANAGEMENT FOR NON-SPECIFIC LOW BACK PAIN - Zermeen Zerish; Zahra Jabeen (Journal of University Medical & Dental College, 2017)
Abstract: Objectives: Examine effects of Exercise therapy and transcutaneous electrical nerve stimulation solo and mutually for treating pain due to NSLBP Methods: 90 patients of age 20-40 years with Non-Specific LBP were randomized into three groups. In first group (1) Transcutaneous Electrical Nerve Stimulation was given and in second group (2) only exercises were given and in third group (3) Both TENS and exercises were given each group included 30 patients. Comparisons among both groups were conducted for variations in pain score and significance difference. Results: Out of 90 subjects. Group having combination of both the treatments shown visible effects in decreasing pain (VAS p<0.05) as compare to other treatment groups whereas after this group TENS group ranked second in effectiveness and lastly exercise therapy is effective which shows that transcutaneous electrical nerve stimulation plus exercise therapy taken together was more effective in managing non-specific low back pain. Conclusion: Owing to the statistical significance difference in current study, and view of sample power due to large number of patients in each group, the results lead to positive conclusion. Therefore, it can be concluded that transcutaneous electrical nerve stimulation plus exercise therapy taken together is more effective. In addition, transcutaneous electrical nerve stimulation used solo and exercise therapy used solo is not as effective as compare to both the treatments taken together as a treatment protocol.